Proceedings of the 17th ACM Conference on Interaction Design and Children 2018
DOI: 10.1145/3202185.3202729
|View full text |Cite
|
Sign up to set email alerts
|

Effects of playful audio augmentation on teenagers' motivations in cooperative physical play

Abstract: Physical Education (PE) is beneficial for students' mental and physical health, however, teenagers are increasingly becoming less motivated to actively participate in the current form of PE. Motivational studies show that collective physical activity augmented by playful interactions could encourage more participation and social engagement in physical activities (PA). In this paper, we present a within-subject field study with 20 teenagers formed into five groups sized equally. The study is conducted using Shu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Further, we also identified studies that showed various ways of expanding or influencing the teaching-learning process. Specifically, the forms of cooperative learning in PE expanded through the use of digital media and could be positively influenced (Ma et al, 2018).…”
Section: Cognitivementioning
confidence: 99%
See 1 more Smart Citation
“…Further, we also identified studies that showed various ways of expanding or influencing the teaching-learning process. Specifically, the forms of cooperative learning in PE expanded through the use of digital media and could be positively influenced (Ma et al, 2018).…”
Section: Cognitivementioning
confidence: 99%
“…Relaxation and expression were positively influenced as were social interaction and perceived competence. However, in the event of failure, there was negative reinforcement (Ma et al, 2018). Meanwhile, Kok et al (2020) examined self-efficacy in dealing with digital media-more precisely with video feedback.…”
Section: Attitudes and Self-efficacymentioning
confidence: 99%
“…. " [25] The concept of enchantment used here comes from David Rose's book Enchanted Objects [30]. Although his focus is not on audio, he discusses at length the idea of using technology to make ordinary objects magical, or to otherwise augment physical objects.…”
Section: Enchanting Silent Physical Objects With Digital Soundmentioning
confidence: 99%